E-development : from excitement to effectiveness - Schware, Robert, 1952- (Books Ser., 2005)
Information and communication technologies (ICTs) are increasingly being recognized as essential tools of development-tools that can empower poor people, enhance skills, increase productivity and improve governance at all levels. The success of ICT-enabled development (or e-development) will thus not be measured by the diffusion of technology, but by advances in development itself: economic growth and, ultimately, achievement of the Millenium Development Goals. This volume examines a wide range of issues related to e-development, with a focus on the requirements and realities of using ICTs to.